PENGEMBANGAN MULTIMEDIA INTERAKTIF MENGGUNAKAN MODEL DRILL AND PRACTICE PADA MATA PELAJARAN IPA KELAS VIII DI SMP - Tiara Dhea Wijaya; Septriyan Anugrah; Rahmi Pratiwi; Alkadri Masnur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the difficulties experienced by eighth-grade students at SMP Pembangunan Laboratorium UNP in remembering and understanding complex science material. This condition indicates the need for repeated practice to strengthen memory and conceptual understanding. Therefore, interactive multimedia learning based on Drill and Practice was developed as a solution to help students understand the material.This research is a type of Research and Development (R&D) with a DDD-E development model that includes the stages of Decide, Design, Develop, and Evaluate. The validity test was conducted by one subject matter expert and two media experts, the practicality test involved 30 eighth-grade students, and the effectiveness test used questions analyzed with the N-Gain formula. Validity and practicality data were obtained through a Likert scale questionnaire.The results showed that the subject matter expert gave an average score of 3.60 (90%) and the media expert gave an average score of 3.92 (98%), which is considered highly valid. The practicality test obtained a percentage of 87.32% (very practical), and the effectiveness test showed an average N-Gain value of 0.57, which is considered moderate. These results indicate that Drill and Practice-based interactive multimedia is feasible, practical, and effective for use in science learning in eighth grade junior high school. Repeated practice in this media helps students strengthen their memory, correct mistakes, and understand concepts more deeply and continuously.